Lucía Hiriart and her intervention in early childhood education during the civil military dictatorship in Chile (1973-1990) - Barco, Blanca; Falabella, Alejandra (Historia y Memoria de la Educación, 2025)
Little is known about the intervention of Lucía Hiriart, wife of the dictator Augusto Pinochet, in early childhood education (0 to 6 years) in Chile. This paper analyzes the transformations of the civil-military dictatorship in this educational level and, especially, the role of Hiriart. The study is based on a documentary analysis and in-depth interviews. The findings show Hiriart’s intervention in the incipient institutionality of early childhood education, the use of female volunteers in order to control the early childhood centers of the National Board of Kindergartens and the centers of the National Foundation for Community Aid, aimed at caring and feeding children. This paper shows the ways Lucía Hiriart used her political power and the volunteers in Chilean early childhood education, producing repercussion sup to nowa days in an institutional fragmented system.